The Gongyang Commentary on The Spring and Autumn Annals A Full Translation - Miller, H.; Miller, H. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
This book is a full translation of the Gongyang Commentary on the Spring and Autumn Annals, a history of the Chinese state of Lu from 722 to 481 BCE, annotated so as to highlight the moral philosophy of its supposed writer, Confucius.